Análisis de los impactos ambientales generados por el derrame de hidrocarburos transportados en buques en el mar Caribe durante las primeras dos décadas del siglo XXI (2022)
Hydrocarbons are essential for the world we know today, since this resource is essential for the generation of electricity, additionally it is a raw material of the first order, which is needed to produce a diversity of substances and materials without which the world would not work as it does in modernity (IGME and ACIEP, 2016). All countries have specific legislation to regulate the extraction, refining, transportation and use of hydrocarbons, since despite the still marked energy dependency on this fossil material, countries are currently building alternatives to move to cleaner energy matrices and less contaminants. The objective of this paper is to analyze the environmental impacts caused by the hydrocarbon spill in the Caribbean Sea, through a retrospective review of accidents that occurred during the first two decades of the 21st century, establishing relationships between these events and non-compliance with the MARPOL International Convention. The document discusses the most important aspects in the process of transporting hydrocarbons through ships, current regulations and the behavior of the protocols provided for in specific cases of hydrocarbon spills in the Caribbean Sea. The social and environmental impacts are significant, and in many cases avoidable, therefore it is expected that the greater the compliance with the protocols, the lower the risk of accidents.